PEMBANGUNAN TRASH TRAP SEBAGAI PELINDUNG LAUT DARI ANCAMAN SAMPAH PLASTIK - Muslihuddin Aini; Zia Zannititah Pawana; Fino Sekar Friandi; M. Zulfian Kurniasaputra; Ahmad Fadli Syarief Zain (Jurnal Abdi Insani, 2023)
Labuhan Haji Beach has a problem with piles of plastic waste on the beach. According to observations made by the Coastal Environmental & Fisheries Research Institute (CEF), the plastic waste found on Labuhan Haji Beach amounts to 9.18 tonnes or around 0.77 kg/m2. Since 2018 efforts have been made by the Government and stakeholders to deal with this problem, starting from making regulations, cleaning up, to anti-plastic waste campaigns. However, these efforts have not had a significant impact both physically and non-physically. The purpose of implementing this dedication is to form institutions within the scope of the Haj harbor community; the creation of trash trap facilities on the river route to Labuhan Haji Beach. The method of implementing this service is divided into 6 (six) activities, namely deliberation and coordination, outreach, making trash traps, installing trash traps, operating trash traps, monitoring and evaluation. This activity is expected to provide a solution to prevent plastic waste from going into the sea. The results achieved in this community service activity were being able to gather several stakeholders such as DLHK of NTB Province, DLHK of East Lombok Regency, Pemdes Labuhan Haji which had never before had joint coordination and deliberation activities in alleviating waste problems at Labuhan Haji Beach, providing outreach to the residents of Labuhan Haji Village who live on the banks of the river, are able to build 1 (one) Trash Trap at the mouth of the Labuhan Haji River which has been able to dispel Â± 10 (ten) tons of waste with a total number of volunteers of 100 people from 10 agencies in the Regency East Lombok. Labuhan Haji Village already has a trash barrier facility in the form of a trash trap. The impact felt after this service activity was carried out was that 90% of the garbage heading to Labuhan Haji Beach could be blocked.